Taxonomy of Iranian Asaccus (Squamata: Phyllodactylidae) with description of a new species from southern Iran - Nazarov, Roman A.; Nabizadeh, Hossein; Rajabizadeh, Mehdi; Melnikov, Daniel A.; Volkova, Valentina R.; Poyarkov, Nikolay A.; Rastegar-Pouyani, Eskandar (Zootaxa, 2024)
We provide the first diversity assessment of Iranian species of the genus Asaccus based on COI DNA-barcoding. We analyzed 53 samples of Iranian Asaccus representing nine OTU corresponding to 10 currently recognzied nominal species, and evaluated both morphological and genetic data to support the recognition of a new species from Bandar-e Jask, Hormozgan Province, southern Iran—Asaccus authenticus sp. nov. The new species is characterized by medium body size (SVL max 55.5 mm), elongated limbs, and relatively small dorsal tubercles arranged in 12–14 regular rows. Morphologically Asaccus authenticus sp. nov. resembles both Arabian and Iranian representatives of the genus; phylogenetically it forms a highly divergent lineage with sister relationships to all other Iranian congeners. We applied the geometric morphometrics method to compare the position and shape of postmental plates for almost all members of Asaccus and evaluated the importance of this character in species diagnostics in this group. We also critically evaluate the recent phylogenetic data on Asaccus and discuss the most problematic questions on taxonomy of this genus. We also revalidate Asaccus ingae (Eiselt, 1973) as a full species; overall our work raises the total number of species of the genus Asaccus to 20.